Perspectives of Targeting mTORC1–S6K1 in Cardiovascular Aging - Ming, Xiu-Fen; Montani, Jean-Pierre; Yang, Zhihong (Frontiers in Physiology, 2012)
The global population aging is accelerating and age-associated diseases including cardiovascular diseases become more challenging. The underlying mechanisms of aging and age-associated cardiovascular dysfunction remain elusive. There are substantial evidences demonstrating a pivotal role of the mammalian target of rapamycin complex 1 (mTORC1) and its downstream effector S6K1 signalling in mammalian lifespan regulation and age-related diseases such as type II diabetes mellitus and cancer. The role of mTORC1-S6K1 in age-related cardiovascular diseases is, however, largely unknown and the available experimental results are controversial. This review article primarily summarizes the most recent advances towards understanding the role of mTORC1-S6K1 in cardiovascular aging and discusses the future perspectives of targeting mTORC1-S6K1 signalling as a healthy lifespan extension modality in anti-aging and anti-cardiovascular aging.